Psychological burden associated with worse clinical outcomes in sarcoidosis. (13th September 2019) - Sharp, Michelle; Brown, Taylor; Chen, Edward; Rand, Cynthia S; Moller, David R; Eakin, Michelle N
Abstract : Introduction: Sarcoidosis is a multisystem granulomatous inflammatory disorder. Sarcoidosis is associated with significant morbidity and rising healthcare utilisation. Patients with sarcoidosis report higher psychological symptoms than the general population. We evaluated the association between depressive and anxiety symptoms and clinical outcomes in patients with pulmonary sarcoidosis requiring treatment. Methods: Adult patients in the Johns Hopkins Sarcoidosis Clinic diagnosed with pulmonary sarcoidosis on treatment were eligible for enrollment. Questionnaires were administered to assess depressive and anxiety symptoms, healthcare utilisation and health-related quality of life (HRQoL). Results: 112 participants were enrolled (57% women, 53% African American, median age: 57 years). 34% of participants screened positive for mild and 20% for moderate–severe depressive symptoms. 25% of participants screened positive for mild and 12% for moderate–severe anxiety symptoms. Participants with moderate–severe psychological symptoms had a higher odds of an emergency department visit in the previous 6 months (8.87 for depressive symptoms and 13.05 for anxiety symptoms) and worse HRQoL compared with participants without psychological symptoms. Participants with moderate–severe depressive symptoms had lower diffusion capacity of the lungs for carbon monoxide % predicted compared with those without depressive symptoms. There was no association between elevated psychological symptoms and the odds of hospitalisation, forced vital capacity % predicted and forced expiratory volume in 1 second % predicted. Conclusion: Psychological symptoms may be associated with worse clinical outcomes in sarcoidosis. Improving the recognition through clinic screening and referral for treatment of depression and anxiety in sarcoidosis may reduce acute healthcare utilisation and improve HRQoL.